A portable library of phosphate‐depletion based synthetic promoters for customable and automata control of gene expression in bacteria. Issue 6 (30th March 2021) - Torres‐Bacete, Jesús; Luís García, José; Nogales, Juan
Summary: Industrial biotechnology gene expression systems relay on constitutive promoters compromising cellular growth from the start of the bioprocess, or on inducible devices, which require manual addition of cognate inducers. To overcome this shortcoming, we engineered an automata regulatory system based on cell‐stress mechanisms. Specifically, we engineered a synthetic and highly portable phosphate‐depletion library of promoters inspired by bacterial PHO starvation system (Pliar promoters). Furthermore, we fully characterized 10 synthetic promoters within the background of two well‐known bacterial workhorses such as E. coli W and P. putida KT2440. The promoters displayed an interesting host‐dependent performance and a wide strength spectrum ranging from 0.4‐ to 1.3‐fold when compared to the wild‐type phosphatase alkaline promoter (P phoA ). By comparing with available gene expression systems, we proved the suitability of this new library for the automata and effective decoupling of growth from production in P. putida . Growth phase‐dependent expression of these promoters could therefore be activated by fine tuning the initial concentration of phosphate in the medium. Finally, the Pliar library was implemented in the SEVA platform in a ready‐to‐use mode allowing its broad use by the scientific community. Abstract : Pi‐starvation synthetic promoters with increased spectrum of activity and broad portability have been constructed and characterized. The promoters were used for decoupling microbial growth from production in an automata and self‐inducible two‐stage biotechnological process using P. putida .